The The Effect of Project-Based Learning Activities on Students’ Learning Engagement and Achievement in English Classroom at Junior High School - I Made Duta Kharisma; Ni Nyoman Padmadewi; Luh Putu Artini (Universitas Islam Negeri Palopo, 2025)
The current research focused on examining the implementation of project-based learning activities to improve students’ learning engagement and learning achievement at Junior High School. Mix-Method approach was adapted by employing sequential explanatory design. There were 62 of eighth-grade students were involved as research samples. They were selected by using cluster random sampling which were divided into control and experimental group. The data were collected from test, questionnaire survey, and interview. The instruments used were speaking and writing rubric assessment, close-ended questionnaire, and interview guide. The quantitative data were analyzed through inferential statistics which was MANOVA analysis meanwhile qualitative data were by adapting Qualitative Data Analysis. The findings revealed that the project-based learning had a significant effect on students’ learning engagement and achievement as well as the implementation was perceived positively by the students.